PHARMACOEPIDEMIOLOGIC ANALYSIS OF HOSPITAL TREATMENT OF PATIENTS WITH CEREBRAL INFARCTION AND ATRIAL FIBRILLATION - N. V. Mikheeva; O. V. Reshetko; N. V. Furman (Столичная издательская компания, 2015)
Aim. To analyze pharmacotherapy of cerebral infarction in patients with atrial fibrillation (AF) in real clinical practice of neurological departments of Saratov hospitals.Material and methods. A retrospective longitudinal pharmacoepidemiologic study was carried out. Medical cards were analyzed in patients with cerebral infarction and atrial fibrillation treated in neurology departments from 01.01.2009 to 31.12.2011.Results. Acetylsalicylic acid was prescribed to 66.7% of patients, warfarin - 3.9%. At that target level of international normalised ratio was reached only in 40% of patients. It has been shown frequent (96%) prescriptions of metabolic, neuroprotective and vasoactive drugs with low level of efficacy evidence. Beta-blockers (in 39.3% of patients) and their combination with digoxin (18.7%) were prescribed for heart rate control.Conclusion. Generally, in real clinical practice doctor's choice of pharmacotherapy of cerebral infarction in patients with AF is not exactly in line with contemporary guidelines. These patients are frequently prescribed drugs with low efficacy and level of evidence.